The Role of Teachers in Active Learning to Enhance Students' Interest in National Integration Material for 10th Grade Students at State Senior High School 1 SIMPANG KANAN - Cici Sutari; Junita Junita; Agus Anjar (Eduvest - Journal of Universal Studies, 2024)
Education encompasses learning experiences occurring in various environments throughout life and can be interpreted as teaching organized in schools as formal educational institutions. Teachers play a crucial role in educating students to develop good character by using varied methods to create an engaging learning atmosphere. One increasingly popular method in educational practice is Active Learning. Learning interest significantly influences the learning process. At SMA Negeri 1 Simpang Kanan, students' interest in Civics, particularly the topic of National Integration, is still low, resulting in poor learning outcomes. This research aims to understand how to increase the interest of 10th-grade students at SMA Negeri 1 Simpang Kanan in the topic of National Integration and to identify factors causing the lack of interest. The research employs a qualitative method with data collection techniques including interviews, documentation studies, and observations. The results show that using Active Learning methods can improve students' learning outcomes in the topic of National Integration, positively impacting their learning interest.